A Correlation Study Between the Efficiency of the Educational Teacher and the Motivation of the Students to Learn the Arabic Language in the "Rawdah Al-Khair" Secondary School of Islamic Probolinggo/دراسة ارتباطية بين كفاءة المعلم التعليمية ودافعية الطلبة على تعلم اللغة العربية في مدرسة "روضة الخير" الثانوية الإسلامية بروبولينجو - Isnol Khotimah (JURNAL IJ-ATL, 2018)
The purpose of this research is to describe the educational efficiency of the Arabic language teacher and what is the link between the educational efficiency of the Arabic language teacher and the motivation of students in learning Arabic language at the "Rawdah Al Khair" Islamic Secondary School.يهدف هذا البحث إلى وصف كفاءة التعليمية لمعلم اللغة العربية وما فيها ووصف ارتباط بين الكفاءة التعليمية لمعلم اللغة العربية ودافعية الطلبة في تعلم اللغة العربية بمدرسة "روضة الخير" الثانوية الإسلامية فربولينجو